Facing up to AIDS
XII, 331 p.
Keywords: Facing up to AIDS is a novel and incisive study of a global plague which continues to threaten to engulf South Africa at this crucial moment in its history. Economists, demographers and health planners present a range of new methods of understanding the likely course of the disease, drawn from the most recent research and thinking by social scientists on the relationship between epidemic disease, economic growth and human resources. South Africa presents a unique opportunity for understanding AIDS, combining as it does Third World problems with a sophisticated infrastructure: the models of demographic projection and economic linkages which are explored here will be of major relevance for examining the socio-economic impact of AIDS in a range of countries in Asia and Latin America. Until medical science comes up with a miracle vaccine, the modification of behaviour is the only defence, and the essays in this volume make a powerful case for putting further resources into the research needed to bring this about.